Innovative credit scheme in Burkina Faso - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Since the droughts of earlier decades there have been great changes in Burkina Faso. Many arable and livestock farmers have had to take up other activities. However, since they have had no resources, they have been unable to support themselves and...